Analisis Strategi Model Portofolio Optimal Pada Bursa Efek Indonesia Dengan Kelompok Indeks LQ-45 Periode 2019-2020 - Chavid Moyo Jaladri; Ari Nurcahyo Darmawan (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2022)
The purpose of this study is to discover how to calculate the ideal portfolio of active LQ-45 stocks using a single index model in order to generate a portfolio with a high level of profit (return) and a low level of risk (risk). LQ-45 shares will be a more promising option than investing in a single sector, as losses in one area can be offset by gains in other sectors. The firms that comprise the LQ-45 index are active equities from a variety of industries, making them an excellent choice as an investment option for building a portfolio. The research technique utilized is quantitative research, often known as the scientific or scientific method, since it adheres to the scientific principles of being concrete or empirical, objective, quantifiable, logical, and methodical. Based on the previous chapter’s discussion, this is to describe the conclusion of the research that can be done by employing the optimal portfolio by using the single index model, as well as the analysis of the research findings. That is, the stocks chosen for determining the best portfolio are those of Jasa Marga Tbk (JSMR) and Bank Negara Indonesia Tbk (BBNI). And it is an ideal portfolio for the proportion of funds that will be formed in Jasa Marga Tbk (JSMR) shares, the majority of which is greater in proportion than the proportion of funds in Bank Negara Indonesia Tbk (BBNI). As a result, the optimal portfolio delivers a level of profit/rate of return that is more than the portfolio risk that the investor will accept. As a result, the portfolio consisting of Jasa Marga Tbk (Persero) and Bank Negara Indonesia (BBNI) shares is available for acquisition.